2003
DOI: 10.1152/jn.00371.2002
|View full text |Cite
|
Sign up to set email alerts
|

Differential Response Properties of IB4-Positive and -Negative Unmyelinated Sensory Neurons to Protons and Capsaicin

Abstract: Activation of unmyelinated (C-fiber) nociceptors by noxious chemicals plays a critical role in the initiation and maintenance of injury-induced pain. C-fiber nociceptors can be divided into two groups in which one class depends on nerve growth factor during postnatal development and contains neuropeptides, and the second class depends on glial cell line-derived neurotrophic factor during postnatal development and contains few neuropeptides but binds isolectin B(4) (IB(4)). We determined the sensitivity of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
117
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(137 citation statements)
references
References 60 publications
18
117
2
Order By: Relevance
“…This differs from results obtained in unidentified DRG neurons, in which Ͻ50% of cells responded to capsaicin (Dirajlal et al, 2003), consistent with studies showing mRNA or IR for TRPV1 in Ͻ50% of DRG neurons (Caterina et al, 1997;Michael and Priestley 1999;Robinson et al, 2004). Similarly, the response to acid appears to be distinct between identified visceral DRG neurons and unidentified DRG neurons.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This differs from results obtained in unidentified DRG neurons, in which Ͻ50% of cells responded to capsaicin (Dirajlal et al, 2003), consistent with studies showing mRNA or IR for TRPV1 in Ͻ50% of DRG neurons (Caterina et al, 1997;Michael and Priestley 1999;Robinson et al, 2004). Similarly, the response to acid appears to be distinct between identified visceral DRG neurons and unidentified DRG neurons.…”
Section: Discussionsupporting
confidence: 70%
“…A previous study of unidentified DRG neurons reported a mixture of transient and sustained acid-sensitive currents, both of which were significantly inhibited by amiloride (Dirajlal et al, 2003), suggesting a significant contribution of ASICs. In addition, the majority of the mouse colon DRG neurons in the present study responded to heat, whereas in a previous study only about half of unidentified DRG neurons were heat sensitive (Nagy and Rang, 1999).…”
Section: Discussionmentioning
confidence: 76%
“…More than 90% of bladder neurons responded to capsaicin with a sustained current, confirming the presence of functional TRPV1 receptors, which have been documented immunohistochemically (Cockayne et al, 2000;Birder et al, 2002). One might expect bladder neurons that responded to capsaicin to also exhibit a sustained current to protons, but neither we nor others (Steen et al, 1992;Dirajlal et al, 2003) found such a relationship. Both the sustained proton-evoked current and capsaicin-activated peak current densities were greater in LS than in TL neurons.…”
supporting
confidence: 63%
“…In a recent analysis of GDNFoverexpressing mice (Zwick et al, 2002), we found an increased number of IB4-positive neurons. Because these neurons are heat sensitive (Stucky and Lewin, 1999;Dirajlal et al, 2003), an increase in the number of TRPV1-positive neurons was also expected in these animals. However, no increase in the number of TRPV1 neurons was observed, and analysis of wild-type mice found that only 6% of mouse DRG neurons were positive for both IB4 and TRPV1 (Zwick et al, 2002).…”
Section: Introductionmentioning
confidence: 96%